Information Cascades in the Laboratory - Anderson, Lisa R.; Holt, Charles A. (American Economic Review, 1997)
When a series of individuals with private information announce public predictions, initial conformity can create an "information cascade" in which later predictions match the early announcements. This paper reports an experiment in which private signals are draws from an unobserved urn. Subjects make predictions in sequence and are paid if they correctly guess which of two urns was used for the draws. If initial decisions coincide, then it is rational for subsequent decision makers to follow the established pattern, regardless of their private information. Rational cascades formed in most periods in which such an imbalance occurred.